Strategy/False-name Proof Protocols for Combinatorial Multi-Attribute Procurement Auction - Suyama, Takayuki; Yokoo, Makoto (Autonomous Agents and Multiagent Systems: Proceedings, 3rd International Joint Conference, New York City, New York, 2004., 2004)
In this paper, we investigate a model of a combinatorial, procurement multi-attribute auction, in which each sales item is defined by several attributes called quality, the buyer is the auctioneer (e.g., a government), and the sellers are the bidders. Furthermore, there exist multiple items and both buyer and sellers can have arbitrary (e.g., substitutable/complementary) preferences on a bundle of items. Our goal is to develop a protocol that is strategy-proof for sellers. We first present a VCG-type protocol. As in a standard combinatorial auction, a VCG-type protocol is not false-name-proof, i.e., it is vulnerable against manipulations using multiple identifiers. Next, we show that any strategy-proof protocol in this model can be represented as a framework called Price-Oriented Rationing-Free (PORF) protocol, in which for each bidder, for each bundle of items, and for each quality, the payment for the bidder is determined independently of his own declaration, and the bidder can obtain a bundle that maximizes his utility independently of the allocations of other bidders. We develop a false-name-proof protocol in this model.